Prevalence of iron deficiency among university kendo practitioners in Japan: an observational cohort study - Takahiro Nabeyama; Yosuke Suzuki; Kana Yamamoto; Michiko Sakane; Yoichiro Sasaki; Haruka Shindo; Morihito Takita; Masahiro Kami (Taylor & Francis Group, 2020)
Background Iron deficiency is widely recognized as being the cause of anemia in athletes, although iron status in athletes of Kendo, a traditional Japanese martial art based on swordsmanship and practiced as an educational sport, has not been widely investigated. Methods We performed a health assessment on anemia and serum ferritin levels, along with nutrient intake evaluation, for Kendo practitioners in a university in Japan. Results A total of 56 Kendo practitioners (39 male and 17 female) aged between 18 and 23 years participated in the study. No individuals exhibited WHO-defined anemia (less than 13 or 12 g/dL of hemoglobin levels in male or female), while hypoferritinemia (less than 30 ng/mL) was found in seven (41%) females but not in males. Significantly higher body mass index was found in the female athletes with hypoferritinemia compared to females with normo-ferritinemia in sub-analysis (median [interquartile range]; 25.6 [24.2, 26.9] versus 22.6 [21.7, 24.1], respectively. p < 0.05). No significant differences in the intake of iron were registered between males and females (with and without hypoferritinemia) using data from a food-frequency questionnaire survey. Conclusion No apparent anemia was found in adolescent Kendo practitioners, although this study confirmed the presence of hypoferritinemia in several female athletes. Careful follow-up, involving both clinical and nutritional assessment, will be necessary for them to prevent progression into anemia. A future study with larger cohorts in multiple sites is warranted to assess the prevalence of iron deficiency for validation and, if necessary, to devise a strategy for improving the iron status in Kendo athletes.